RELASI MAKNA SELFIE DENGAN HADIS TENTANG RIYA’ DALAM PERPEKTIF MAHASISWA ILMU HADIS IAIN KEDIRI - Hanik, Umi (IAIN Kediri, 2019)
Increasing technological advances in life encourage people to continue to follow. As the development of the era then the more advanced technology tools. One of them is the presence of gadgets that can be used berselfie. Selfie is a self-image taking activity through a smartphone or webcam which is then uploaded to social media. This study aims to determine the meaning of selfie in social media according to students of Hadith Science IAIN Kediri which is also related to their understanding to the hadith of riya’. Therefore, a qualitative approach isused with in-depth interview method to 13 selected informants. The result of descriptive analysis of berselfie practice in social media by students of Hadith Study Program IAIN Kediri is related with the hadith about riya‘show different meaning. Five informants interpret selfie as amaliyah to self-exist; satisfy desire or desire; as a means of expression in a moment or activity to be seen and remembered at other times by self or others; andpose and expression in front of the camera. Nine informants claimed to be familiar with the hadith about riya’. Seven informants meaning selfie images uploaded in social media is not necessarily related to riya’ behavior because it all depends on how and how often we selfie and the intention of the culprit.Keywords : Meaning; Selfie; Riya’; Social Media.